Identitas nasional dalam pusaran globalisasi dan digitalisasi: Kajian kritis atas jati diri bangsa di era modern - shihab, akbar (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the dynamics of Indonesian national identity amid the rapid development of globalization and digitalization in the modern era. Globalization has created unlimited cultural interaction, while digitalization has accelerated the spread of information, values, lifestyles, and communication patterns in society. These conditions provide positive impacts in the form of scientific and technological progress, but they also create serious challenges to the sustainability of national identity, especially among young generations who are closely connected to digital media. This research uses a library research method with a qualitative descriptive approach through the analysis of books, scientific journals, and academic articles related to national identity, globalization, and digital transformation. The findings indicate that Indonesian national identity is dynamic and continuously adapts to global developments. Pancasila, local culture, character education, and digital literacy play important roles in maintaining national identity. This study recommends strengthening nationalism-based character education and encouraging the positive use of digital media as strategic efforts to preserve Indonesian national identity in the modern era.